A Comparative Histological And Histochemical Study Of The Tongue Of Local Adult Ducks And Geese (NTU Journal of Agriculture and Veterinary Science, 2023)
Our study aimed to determine the histological and histochemical composition of the tongue of both ducks (Anas Platyrhynchos) and geese (Anserini). Our histological study showed that the mucous membrane covering the tongue in local ducks and geese consists of a multi-layered epithelium covering the lamina propria, which differs in the degree of keratinization according to its location in the tongue, and that the thickness of the epithelium of the dorsal surface of the tongue gradually decreases from the front towards the root, while the epithelium increases in thickness towards the root. The ossified epithelium is located at the top and beginning of the body of the tongue, forming what is known as the nail of the tongue in both ducks and geese. The small and large conical papillae in various parts of the tongue, as well as the filiform papillae, are covered with erosive ossified epithelium